Injecting Health Information? The Channeled Role of Radio Personalities in the Vaccination Status of Older Adults - Villarin, Larry V. (Philippine Social Science Journal, 2022)
On top of the country’s predicament to bolster the number of vaccinated older adults is the perpetuating transmission of health mis- and disinformation. Following the approach of Grounded Theory, this study examined the role of radio personalities in the vaccination status of older adults drawing from the data of the 14 semi-structured interviews: seven vaccinated and seven unvaccinated. The study found that radio personalities contribute to their attitudes and behavior about the COVID-19 vaccines. The recurring information learned by older adults from them led to the discovery of wired and unwired trusts, placing both agents in the line of responsibility. This interpretation was derived from the dominant themes emanated by the channel of motivation, views toward radio personalities, emerging mis- and disinformation, credibility indicators, and substantiating information. The study recommended a full-swing collaboration between radio entities and health agencies to increase vaccination uptake among older adults.